THE EFFECT OF EMOTIONAL INTELLIGENCE ON STUDENTS’ MATHEMATICS LEARNING OUTCOME AT GRADE IV SD NEGERI 173418 POLLUNG - Srinarika Nadeak; Reflina Sinaga; Saut Mahulae (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to determine the effect of emotional intelligence on students' mathematics learning outcomes at grade IV of SD Negeri 173418 Pollung in Academic Year 2019/2020. The population of this research was all students of SD Negeri 173418 Pollung, consisting of 362 students, while the samples were selected by purposive sampling technique and the researchers chose grade IV, consisting of 40 students as samples in this study. In this research, the researchers used a quantitative method similar to survey. Then, the hypotheses were tested by using t test. The results of this research indicated that the average value of students’ emotional intelligence was 87.9 with Fair category and the average score of learning outcome was 71.375 with Less category. This was supported by the results of t test in which the value of tcount > ttable which was 1.703 > 1.677. Thus, Ha was accepted, indicating that there was a significant influence of emotional intelligence on the students’ mathematics learning outcomes at grade IV SD Negeri 173418 Pollung Academic Year 2019/2020.